2013
DOI: 10.1111/cen.12184
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue is significantly associated with hearing thresholds in adult women

Abstract: Our findings show an association between VAT and hearing impairment in women. A reduction in visceral adiposity may help to prevent hearing loss in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
0
22
0
4
Order By: Relevance
“…In an animal study, obesity could exacerbate the hearing impairment with elevated hearing thresholds31. In humans, central obesity (i.e., either a higher amount of visceral adipose tissue or a greater WC), was found to be related to an elevated hearing threshold3233. There is also evidence indicating that oxidative stress is a critical factor that links obesity with its associated complications16.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study, obesity could exacerbate the hearing impairment with elevated hearing thresholds31. In humans, central obesity (i.e., either a higher amount of visceral adipose tissue or a greater WC), was found to be related to an elevated hearing threshold3233. There is also evidence indicating that oxidative stress is a critical factor that links obesity with its associated complications16.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was found to be associated with hearing loss in both humans and animals [ 34 , 35 ]. Moreover, it was proposed that central obesity, as well as an increased waist circumference or content of visceral adipose tissue, was significantly associated with an increased hearing threshold after adjusting for body mass index [ 36 , 37 ]. In the present study, we also observed that an increased waist circumference was significantly associated with an increase high-PTA threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The β-CG-fed mice exhibited less body weight gain than control mice, despite comparable food intake. Recent epidemiological studies have associated obesity with the severity of hearing loss [ 4 , 5 ]. Diet-induced obesity exacerbates auditory degeneration in mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age-related hearing impairment (ARHI) is common in older populations, with an estimated prevalence of 30–60%; it has a strong influence on quality of life [ 1 3 ]. Recently, higher body mass index (BMI) and waist circumference have been associated with the severity of hearing loss [ 4 , 5 ]. Obesity-related disorders including dyslipidemia and type 2 diabetes are also associated with ARHI [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%